Perancangan Sistem Keamanan File Transfer Protocol Dengan Secure Socket Layer Pada Server Centos 7 - Alexander Theo Philus Tambunan; Adi Prijuna Lubis; Syartika Anggraini (LPPM STMIK Royal Kisaran, 2021)
Abstract: An advancement in communication technology currently has an influence on developments in data management in the joints of life, making the need for a media center something a must in digital archive storage. Data will not always be stored in personal computers, but it would be better if there was a centralized data container to be a solution in storage media, in order to prevent data loss or data backup. The term network (network) is used when there are at least two or more devices that are connected to one another. To carry out data exchange in this network, a protocol is used that specifies how data is exchanged, and one of the most widely used protocols is the File Transfer Protocol (FTP). FTP is generally useful as a means of exchanging files or data in a network. The FTP protocol is not secure enough, because when data transfer there is no security to protect it. Therefore the FTP protocol is necessary for additional security, by implementing the SSL security protocol or Secure Socket Layer Security protecting the FTP protocol during data transfer. SSL certificates are used for the purpose of handling the security of data packets transmitted over the network system. When SSL is activated, the server and client when the connection occurs will be encrypted so that the data cannot be seen by others. Keywords: FTP; Network; Server; SSL Abstrak: Suatu Kemajuan teknologi komunikasi saat ini memiliki pengaruh terhadap perkembangan didalam pengelolaan data didalam sendi kehidupan, membuat kebutuhan akan media center menjadi sesuatu yang harus dalam penyimpanan arsip digital. Data tidak selamanya akan tersimpan di dalam personal computer saja tetapi akan lebih baik jika ada wadah data terpusat menjadi solusi dalam media penyimpanan, agar menjaga dari kehilangan data atau cadangan data. Istilah jaringan (network) dipakai apabila terdapat minimal dua atau lebih perangkat yang terhubungkan satu dengan yang lainnya. Untuk melaksanakn pertukaran data didalam jaringan ini, digunakan protocol yang menspesifikasikan bagaimana data dipertukarkan, dan salah satu protocol yang banyak digunakan adalah File Transfer Protocol (FTP). FTP umumnya bermanfaat sebagai sarana pertukaran file atau data dalam suatu network. Protokol FTP tidaklah cukup aman, dikarenakan ketika transfer data tidak ada keamanan untuk melindunginya. Maka dari itu protokol FTP perlu untuk penambahan keamanan, dengan menerapkan protokol keamanan SSL atau Secure Socket Layer Security melindungi protokol FTP pada saat transfer data. Sertifikat SSL dimanfaatkan untuk keperluan menangani keamanan paket data yang ditransmisikan melalui sistem jaringan. Ketika SSL diakatifkan, maka server dan client ketika terjadi koneksi akan ter enkripsi sehingga data yang ada tidak dapat untuk dilihat oleh orang lain. Kata kunci: FTP;Network; Server; SSL